Study of Drainage Channel Capacity on Jalan Masangan Kulon Sukodono Sidoarjo - Brian Okta Vyanto Eky Mahendra; Iwan Wahjudijanto; Novie Handajani (Jurnal Syntax Transformation, 2023)
A problem often faced by people in urban areas is flooding in residential areas during the rainy season. The causes of flood inundation include land conversion, which was originally an open area turned into a built-up area for settlements, industry or trade and offices. Land use that is not orderly causes the issue of drainage channel capacity in urban areas to be very complex. This study aims to assess the capacity of drainage channels located on Jalan Masangan Kulon so as not to hamper traffic flow and harm the activities of the surrounding community and the handling carried out to overcome flooding in the existing. The method of calculating the flood plan for this drainage case study uses the Rational Method with a 2-year return period. Data collection is done by observation, taking measurements and channel normalization. Evaluation of channel capacity is carried out to assess the ability of drainage channels to plan discharge. The results obtained in this study Flood discharge in the upstream river with a return period of 2 years amounted to 1.54 m³/second. Areas that experience flooding occur in Segments 10-17 and 18-19. In segment 10-17 the block discharge is 3.98 m³/second and the existing discharge is 3.389 m³/second. After normalizing the existing discharge is 4.34 m³ / second. In segments 18-19 the block discharge is 5.228 m³/second and the existing discharge is 4.647 m³/second. After normalizing the existing discharge is 5.760m³/second.